21st-century climate change around Kangerlussuaq, west Greenland: From the ice sheet to the shores of Davis Strait. Issue 1 (1st January 2018) - Boberg, F.; Langen, P. L.; Mottram, R. H.; Christensen, J. H.; Olesen, M.
ABSTRACT: Using regional climate-model runs with a horizontal resolution of 5.5 km for two future scenarios and two time slices (representative concentration pathway [RCP] 4.5 and 8.5; 2031–2050 and 2081–2100) relative to a historical period (1991–2010), we study the climate change for the Qeqqata municipality in general and for Kangerlussuaq in particular. The climate-model runs are validated against observations of temperature and surface mass balance and a reanalysis simulation with the same model setup as the scenario runs, providing high confidence in the results. Clear increases in temperature and precipitation for the end of the 21st century are shown, both on and off the ice sheet, with an off–ice sheet mean annual temperature increase of 2.5–3°C for the RCP4.5 scenario and 4.8–6.0°C for the RCP8.5 scenario, and for precipitation an increase of 20–30% for the RCP4.5 scenario and 30–80% for the RCP8.5 scenario. Climate analogs for Kangerlussuaq for temperature and precipitation are provided, indicating that end-of-the-century Kangerlussuaq mean annual temperature is comparable with temperatures for the south of Greenland today. The extent of glacial retreat is also estimated for the Qeqqata municipality, suggesting that most of the ice caps south of the Kangerlussuaq fjord will be gone before the end of this century. Furthermore, the high-resolution runs are compared with an ensemble of six models run at a 50 km resolution, showing the need for high-resolution model simulations over Greenland.